The driver of global agricultural value chains: Evidence from 6 ASEAN Countries - Muhammad Firdaus; Anny Ratnawati; Ariyo Dharma Pahla Irhamna; Bustanul Arifin (Regional Development Information Center, Universitas Sebelas Maret, 2025)
This study investigates the drivers of global agricultural value chain (GAVC) participation in six ASEAN countries: Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam. Employing panel geographically weighted regression, the paper analyzes the spatial heterogeneity of factors influencing global agricultural value chain participation. Our findings reveal significant variations in the impact of tariffs, FDI, agricultural land area, inland waters, and trade balance across countries. Tariffs emerge as a crucial factor in enhancing competitiveness in Indonesia, Singapore, and Thailand, aligning with trade theory. FDI positively influences Malaysia's global agricultural value chain participation, emphasizing attracting foreign investment. Agricultural land area plays a pivotal role in Indonesia and Thailand, highlighting the significance of resource endowments. Inland waters contribute significantly to agriculture in the Philippines, while their impact in Indonesia suggests potential inefficiencies in water management. Trade balance in food products positively affects global agricultural value chain involvement in Thailand and Vietnam. These findings underscore the need for tailored policies to address the unique characteristics of each ASEAN country. Future research should explore the long-term implications of these factors and consider broader socio-economic and environmental contexts.